On the rise and fall of the apnea−hypopnea index: A historical review and critical appraisal. (14th May 2020) - Pevernagie, Dirk A.; Gnidovec‐Strazisar, Barbara; Grote, Ludger; Heinzer, Raphael; McNicholas, Walter T.; Penzel, Thomas; Randerath, Winfried; Schiza, Sophia; Verbraecken, Johan; Arnardottir, Erna S.
Summary: The publication of "The Sleep Apnea Syndromes" by Guilleminault et al. in the 1970s hallmarked the discovery of a new disease entity involving serious health consequences. Obstructive sleep apnea was shown to be the most important disorder among the sleep apnea syndromes (SAS). In the course of time, it was found that the prevalence of obstructive sleep apnea reached the proportions of a global epidemic, with a major impact on public health, safety and the economy. Early on, a metric was introduced to gauge the seriousness of obstructive sleep apnea, based on the objective measurement of respiratory events during nocturnal sleep. The apnea index and later on the apnea−hypopnea index, being the total count of overnight respiratory events divided by the total sleep time in hours, were embraced as principle measures to establish the diagnosis of obstructive sleep apnea and to rate its severity. The current review summarises the historical evolution of the apnea−hypopnea index, which has been subject to many changes, and has been criticised for not capturing relevant clinical features of obstructive sleep apnea. In fact, the application of the apnea−hypopnea index as a continuous exposure variable is based on assumptions that it represents a disease state of obstructive sleep apnea and that evocative clinical manifestations are invariably caused by obstructive sleep apnea if the apnea−hypopnea index is above diagnostic threshold. A critical appraisal of the extensive literature shows that both assumptions are invalid. This conclusion prompts a reconsideration of the role of the apnea−hypopnea index as the prime diagnostic metric of clinically relevant obstructive sleep apnea.